MENINGKATKAN MINAT BELAJAR SENI TARI MELALUI PENERAPAN TEKNIK GERAK DASAR TRADISIONAL PADA SISWA KELAS IV SD NEGERI 114 PINCARA - Tiriwan; Abrina Maulidnawati Jumrah; Mulyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low interest in learning dance among fourth-grade students at SD Negeri 114 Pincara. Students tend to be less enthusiastic and less motivated when participating in dance learning activities. This study aims to increase students' interest in learning dance through the application of traditional basic movement techniques. The method used in this research is Classroom Action Research (CAR) which refers to the Kemmis and McTaggart model, consisting of two cycles with four stages: planning, implementation, observation, and reflection. The subjects of this study were 24 fourth-grade students at SD Negeri 114 Pincara. Data collection techniques used observation sheets, questionnaires, and documentation. The results showed that the application of traditional basic movement techniques could increase students' interest in learning dance. In the pre-cycle, the percentage of students' interest in learning was 45.8% in the low category. After the implementation of Cycle I, it increased to 66.7% in the medium category, and in Cycle II it increased to 87.5% in the high category. Thus, it can be concluded that the application of traditional basic movement techniques can increase the interest in learning dance of fourth-grade students at SD Negeri 114 Pincara.